2021
DOI: 10.3390/pr10010008
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on UV-AOPs for Efficient Continuous Flow Removal of 4-tert-Butylphenol

Abstract: In the present study, UV-light-driven advanced oxidation processes (AOPs) have been employed for the degradation of 4-tert-Butylphenol (4-t-BP) in water under continuous flow conditions. The effects of varying space time (10, 20, 40, 60 and 120 min) and oxidant dosage (88.3 mg/L, 176.6 mg/L and 264 mg/L) were examined. 4-t-BP degradation efficiency in the UV-induced AOPs followed the order of UV/H2O2 (264.9 mg/L) ≈ UV/Fe2+/H2O2 > UV/Fe3+/H2O2 > UV/H2O2 (176.6 mg/L) > UV/H2O2 (88.3 mg/L) > UV/Fe-TiO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…For the case of gamma radiation, the model adequately describes the experiment according to Equation (19) with a correlation coefficient of 0.99. All coefficients of the model are significant for a significance level of less than 0.05. and [H2O2] the concentration of H2O2.…”
Section: Effect Of the Fenton Reagent On The Degradation Of Dzp By So...mentioning
confidence: 99%
See 1 more Smart Citation
“…For the case of gamma radiation, the model adequately describes the experiment according to Equation (19) with a correlation coefficient of 0.99. All coefficients of the model are significant for a significance level of less than 0.05. and [H2O2] the concentration of H2O2.…”
Section: Effect Of the Fenton Reagent On The Degradation Of Dzp By So...mentioning
confidence: 99%
“…Considering the high impact of pharmaceutical products, it is very important to remove them from the wastewater before discharge. Several researches carried out in recent years point to the use of advanced oxidation processes (AOPs) as innovative technologies for the elimination of persistent pollutants [6,[15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Obviously, a higher space time enhances the generation of radical oxidative species and improves thus the TOC removal. Mergenbayeva and Poulopoulos reported that increasing the space time from 10 min to 120 min under UV radiation caused the 4-tert-butylphenol degradation enhancement from 46% to 84% [56]. Both space time and residence time significantly impact the kinetics of the process [57].…”
Section: Three-dimensional Plots For the Rsm Modelmentioning
confidence: 99%
“…Advanced oxidation processes (AOPs) could provide interesting solutions to this problem. AOPs are a large class of oxidative techniques that mainly rely on the production of hydroxyl ( • OH) and sulfate radicals (SO4 •-) [9,10]. Among different AOPs, heterogeneous photocatalysis receives great attention from researchers due to the convenient separation and possible reuse of the photocatalyst [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…AOPs are a large class of oxidative techniques that mainly rely on the production of hydroxyl ( • OH) and sulfate radicals (SO4 •-) [9,10]. Among different AOPs, heterogeneous photocatalysis receives great attention from researchers due to the convenient separation and possible reuse of the photocatalyst [10,11]. Photocatalysts can be activated by light, which results in oxidation of the electron hole in the valence band and reduction of the electron in the conduction band.…”
Section: Introductionmentioning
confidence: 99%